Effect of nitrogen on the properties of nanostructured zinc nitride heterojunction prepared by reactive magnetron sputtering. (July 2022) - Addie, Ali J.; Mohammed, Mudhafar A.; Ismail, Raid A.
Abstract: In this work, zinc nitride (Zn3 N2 ) thin film was deposited on glass and silicon substrates by DC reactive magnetron sputtering technique. The structural, optical and electrical properties of Zn3 N2 films at various nitrogen gas concentration were investigated. XRD results of the as-deposited films confirm the formation of crystalline cubic anti -bixbyite Zn3 N2 structure with a preferred orientation along (400) plane. AFM and SEM have used to study the surface topography and morphology of the deposited film. Raman analysis of the as-grown films show two broad peaks at 265 and 567 cm −1 related to the Raman-active modes in the Zn3 N2 compound. The highest optical transmittance of the film was 62% for the film deposited with pure nitrogen and decreased to 1% at 40% N2 . There was a blueshift in the absorption edge with increasing the N2 gas concentration. The direct optical band gap of the films ranged from 1.27 to 2.1 eV with increasing N2 gas flow. The I–V characteristics of Zn3 N2 /p-Si heterojunctions showed rectification characteristics. C–V results showed that the built-in-potential of the heterojunctions was in the range of 0.51–0.82V. A broad responsivity has been observed for all of Zn3 N2 /p-Si heterojunction photodetectors and the highest spectral responsivity and quantum efficiency of the photodetector are 0.15 A/W and 35% at 600 nm, respectively.